Appropriate vancomycin use in a Malaysian tertiary hospital based on current HICPAC recommendations - Farida Islahudin; Hui-Yeah Ong (Journal of Infection in Developing Countries)
Introduction: Antibiotic resistance is a rapidly emerging problem. A major concern is methicillin-resistant Staphylococcus aureus (MRSA), especially in developing countries where cost-effectiveness is imperative. Restriction of vancomycin usage is necessary to reduce the emergence of vancomycin-resistant organisms. The aim of this study was to look into the appropriate use of vancomycin based on the Healthcare Infection Control Practices Advisory Committee (HICPAC) guidelines and to investigate serum levels of vancomycin. Methodology: The study was performed retrospectively. Medical records of patients treated with vancomycin for the past year were identified and selected. Results: Overall, 118 patients were treated with vancomycin. Appropriate use of vancomycin was significantly higher than inappropriate use (p = 0.001). Approximately 85% (n = 100) of patients were given vancomycin for treatment, whereas the rest were given it for prophylaxis. Appropriate use of vancomycin was observed in 67% (n = 79) of patients. However, there was still a high rate of inappropriate vancomycin use for prophylaxis and treatment (n = 39, 33.1%). The most common reason for inappropriate use was non-neutropenic and non-line related sepsis (n = 36, 30.8%). Therapeutic drug monitoring of vancomycin was performed in 79 patients (67%). Most patients (n = 53, 67%) demonstrated sub-therapeutic levels during the first measurement. There was no significant difference between trough levels achieved with a higher (> 15 mg/kg) versus a lower dose (< 15 mg/kg). Conclusions: This study demonstrates that there was still a high level of inappropriate vancomycin use, which could potentially contribute to vancomycin resistance.